Contribution Des Footballeurs Africains Sur Le Niveau De Jeu En Europe (Global Journal of Human-Social Science, 2021)
The objective of this study is to highlight the contribution of African footballers on the level of game in Europe To achieve this objective we used a hypothetico-deductive method which consists in constructing responses to the phenomenon studied on the basis of theoretical or empirical literature This method was supplemented by the presentation of some statistics obtained after using the website of FIFA International Federation of Association Football UEFA Union of European Football Associations and CIES International Centre for Sports Studies It has been noted that from the 1980s to the present day several African players have contributed to effectively raising the standard of football in Europe Indeed several African players have scored goals in the final of Europe s most prestigious club competition In addition at least fifteen Africans have won a C1 final
Keywords: africa; footballers; game; Europe